CORRELATION OF EXCLUSIVE BREASTFEEDING AND CIGARETTE SMOKE EXPOSURE WITH PNEUMONIA IN CHILDREN UNDER TWO YEARS - Denisca Vanya Almeida; Fariani Syahrul (Jurnal Berkala Epidemiologi, 2020)
Background: Pneumonia is one of the leading causes of death for children and is caused by pneumococcus, staphylococcus, and streptococcus bacteria. Exclusive breastfeeding and exposure to cigarette smoke are risk factors for pneumonia in children less than two years old. Purpose: The aim of this research was to analyze the relationship between exclusive breastfeeding or exposure to cigarette smoke and pneumonia in children aged less than two years at Public Health Center (PHC) of Wates, Kediri District. Methods: This research employed analytic observational research using a case–control research design. The number of research samples used was 60, consisting of 30 case respondents and 30 control respondents. The samples were taken in the PHC of Wates, Kediri District’s working area in July 2019. The determination of the samples was carried out through simple random sampling. The data were analyzed using chi-square analysis. Results: The research variables related to pneumonia in children less than two years old at PHC of Wates, Kediri District were exclusive breastfeeding with Odds Ratio (OR) = 3.50 (95% Confidence Interval (CI) = 1.20–10.19), the age of the mothers of the two-year-old infants with OR = 0.19 (95% CI = 0.04–0.78), and the education of the mothers of children less than two years old with OR = 3.14 (95% CI = 1.07–9.27). Conclusion: Exclusive breastfeeding, maternal age, and mothers’ level of education are some of the risk factors for pneumonia. The suggestion from this research is to hold socialization in the form of pneumonia prevention, education on exclusive breastfeeding for mothers who have children under two years of age, and the dangers of smoking for children's health.